Optimal antithrombotic therapy in ischemic stroke patients with non-valvular atrial fibrillation and atherothrombosis: study protocol for a randomized controlled trial - Okazaki, Shuhei; Yamamoto, Haruko; Asakura, Koko; Omae, Katsuhiro; Maeda, Hirotada; Tanaka, Kanta; Yamamoto, Shiro; Hirano, Teruyuki; Iguchi, Yasuyuki; Sakaguchi, Manabu; Koga, Masatoshi; Ihara, Masafumi; et al. (Frontiers in Neurology, 2024)
The addition of antiplatelet therapy to anticoagulant therapy in patients with stroke with non-valvular atrial fibrillation (NVAF) and atherothrombotic disease may increase bleeding risk without reducing recurrent stroke risk. Aims: To evaluate the clinical benefits of anticoagulant monotherapy compared to combination therapy with anticoagulants and antiplatelet agents. Methods and design: This is an investigator-initiated prospective multicenter, randomized, openlabel, parallel-group clinical trial. Patients with NVAF and atherothrombotic disease who have had a recent ischemic stroke or transient ischemic attack will be eligible to participate in this trial. Study outcomes: The primary outcome is a composite of ischemic cardiovascular events, including cardiovascular death, ischemic stroke, myocardial infarction, systemic embolism, ischemic events requiring urgent revascularization, and major bleeding events within 2 years after randomization. Sample size estimates: This study will enroll 400 patients, 200 receiving anticoagulant monotherapy and 200 receiving combination therapy. This sample size will provide 90% power (one-sided P=0.025) to detect a risk reduction in outcome events within 2 years, assuming event rates of 13% and 27% for each group, respectively, and a 10% loss to follow-up at a 2.5% significance level with one-sided log-rank tests at an interim analysis and a final analysis. Discussion: This will be the first study to assess the net clinical benefit of oral anticoagulant monotherapy in ischemic stroke patients with NVAF and atherothrombosis.